1997
DOI: 10.1023/a:1008247428385
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase activity in epithelial ovarian cancer: Association with response to chemotherapy and disease outcome

Abstract: A direct association between high GST activity and a better clinical outcome in terms of response to chemotherapy and survival has been observed in a large series of primary untreated ovarian cancer patients. These results, which are contrary to the expectations raised by in vitro studies, emphasize the need for caution when translating in vitro-generated hypotheses to the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Several studies clearly show an inverse correlation between GST-P expression and cancer. In studies of esophageal adenocarcinoma and ovarian cancer, the tumor tissue showed lower GST-P levels in tumor tissue than in the surrounding normal tissue (34,35). The current studies on canine lymphoma agree in that GST-P was observed more frequently in the normal lymph nodes.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies clearly show an inverse correlation between GST-P expression and cancer. In studies of esophageal adenocarcinoma and ovarian cancer, the tumor tissue showed lower GST-P levels in tumor tissue than in the surrounding normal tissue (34,35). The current studies on canine lymphoma agree in that GST-P was observed more frequently in the normal lymph nodes.…”
Section: Discussionsupporting
confidence: 72%
“…For example, marked overexpression of GST P1-1 has been observed following the exposure of several tumor cell lines to various tumor drugs [5] and hence the enzyme is used as a biomarker. GST P1-1 is also overexpressed in CPT-resistant cell lines [10,11] and the inhibition of the enzyme has been shown to reverse resistance. [6] In addition, GST P1-1 knockout mice are considerably more sensitive to the cytotoxic effects of CPT treatment than their wild-type counterparts.…”
Section: Abstract: Antitumor Agents · a C H T U N G T R E N N U N G Dmentioning
confidence: 99%
“…50,52 Studies that examine associations within specific histologic types of ovarian cancer are a promising area for further research.…”
Section: Disease Associationsmentioning
confidence: 99%